2021
DOI: 10.3390/microorganisms9010184
|View full text |Cite
|
Sign up to set email alerts
|

Blastocystis sp. Prevalence and Subtypes Distribution amongst Syrian Refugee Communities Living in North Lebanon

Abstract: Molecular data concerning the prevalence and subtype (ST) distribution of the intestinal parasite Blastocystis sp. remain scarce in the Middle East. Accordingly, we performed the first molecular epidemiological survey ever conducted in the Syrian population. A total of 306 stool samples were collected from Syrian refugees living in 26 informal tented settlements (ITS) subjected or not to water, sanitation, and hygiene (WASH) interventions in North Lebanon, then screened for the presence of Blastocystis sp. by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 53 publications
(68 reference statements)
5
24
0
Order By: Relevance
“…These observations support the historical findings on abundance of Blastocystis in developing countries owing to poor personal hygiene, unsanitary living conditions, consumption of contaminated food and water, and exposure to animals [9,27,28]. Moreover, the prevalence of Blastocystis reported in this study is consistent with previous studies done in developing world [4,29,30]. Blastocystis is transmitted through fecal-oral route.…”
Section: Discussionsupporting
confidence: 92%
“…These observations support the historical findings on abundance of Blastocystis in developing countries owing to poor personal hygiene, unsanitary living conditions, consumption of contaminated food and water, and exposure to animals [9,27,28]. Moreover, the prevalence of Blastocystis reported in this study is consistent with previous studies done in developing world [4,29,30]. Blastocystis is transmitted through fecal-oral route.…”
Section: Discussionsupporting
confidence: 92%
“…To complete our data and taking advantage of the large number of isolates subtyped in the present survey, the intra-ST variation observed within the 3 major STs identified in the Guinean population was analyzed. This analysis succeeded those recently performed in Senegal [10] and among Syrian refugees leaving in North Lebanon [41] using the same molecular marker and comparing the sequence of the same amplified domain. By first determining the genotypes for each of these 3 STs through the identification of the variable positions between sequences of isolates belonging to the same ST and, then, by establishing the ratio of the number of isolates per genotype, it was shown that ST3 exhibited the lowest intra-ST diversity followed by ST2 and ST1 in the Senegalese and Syrian cohorts [10,41].…”
Section: Discussionsupporting
confidence: 64%
“…The amplified fragment of approximately 300 bp length of the SSU rDNA gene has been shown to contain sufficient sequence information for accurate subtyping of Blastocystis sp. isolates [10,13,38,41,44]. Both positive (DNA obtained from Blastocystis sp.…”
Section: Dna Extraction and Molecular Subtyping Of Blastocystis Sp Is...mentioning
confidence: 99%
See 2 more Smart Citations